Utilization of Azolla microphylla as Nitrogen Source in Nata de Coco Production Affected by Various Fermentation Conditions - Husna, Afifa; Reviana, Nanda; Pradita, Shelly; Saati, Elfi; Siskawardani, Devi; Fahmi, Ilmam (JURNAL AGROINDUSTRI HALAL, 2025)
Ammonium sulfate (ZA) is commonly used as a nitrogen source in nata de coco production. However, its synthetic nature may leave harmful residues with long-term consumption. In this study, the floating aquatic plant Azolla microphylla was investigated as a natural alternative nitrogen source to replace ZA. The experiment evaluated the influence of fermentation temperature (26.3 °C and 30 °C), types of carbon sources (sucrose, glucose, fructose, and lactose), sugar concentrations (2%, 4%, 6%, and 8%), and starter concentrations (5% and 10%) on nata de coco production using A. microphylla as the nitrogen source. The results demonstrated that among the carbon sources tested, fructose at an incubation temperature of 30 °C was the most effective in supporting optimal nata formation, in terms of yield (39.08 %), thickness (1.15 cm), and crude fiber (8.59 %). Meanwhile, the combination of 6% sugar and 10% starter concentration produced the best nata de coco in terms of thickness (1.20 cm), yield (33.05 %), crude fiber content (8.69 %), and hardness value (8.34 N). This study confirms the potential of Azolla microphylla as a promising alternative to ammonium sulfate in nata de coco fermentation under well-optimized conditions.